2011
DOI: 10.1038/jp.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Why do families of sick newborns accept hospital care? a community-based cohort study in Karachi, Pakistan

Abstract: ObjectiveSick young infants are at high risk of mortality in developing countries but families often decline hospital referral. Our objective was to identify the predictors of acceptance of referral for hospital care among families of severely ill newborns and infants <59 days old in three low-income communities of Karachi, Pakistan.Study designA cohort of 541 newborns and infants referred from home by community health workers doing household surveillance, and diagnosed with a serious illness at local communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
1
42
2
Order By: Relevance
“…Delay in seeking care seems to be the most likely reason for this high rate. Due to multiple social, cultural, and financial constraints, care seeking is delayed as evidenced by recent data from Pakistan [15]. Lack of recommendation of the varicella vaccine in the national immunization schedule increases the risk of exposure in these high-risk children as evidenced by reports from countries where susceptible children one year of age and older in the general population are routinely vaccinated [13,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Delay in seeking care seems to be the most likely reason for this high rate. Due to multiple social, cultural, and financial constraints, care seeking is delayed as evidenced by recent data from Pakistan [15]. Lack of recommendation of the varicella vaccine in the national immunization schedule increases the risk of exposure in these high-risk children as evidenced by reports from countries where susceptible children one year of age and older in the general population are routinely vaccinated [13,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, up to three-quarters of families of sick young infants in Karachi, Pakistan, refuse hospital referrals, despite free transport and treatment, because of the substantial opportunity costs to very poor families of prolonged admissions at locations far from their place of residence 3 . Stated reasons for refusal are financial constraints, cultural beliefs, and concern about poor quality of care at hospitals 3, 4. Similar constraints to optimum care of sick newborn babies in high-mortality settings have also been noted from other low-resource settings 5 …”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been found in Bangladesh, Pakistan, Nepal and Tanzania. [38][39][40] Recently, Owais et al 41 reported on care-seeking characteristics of families who have infants with possible serious bacterial infection in Pakistan. Factors associated with seeking care from skilled HCP included recognition by the mother of severity of illness, families able to speak the dominant language spoken in the hospital and the presence of fever or grunting in the child.…”
Section: Local Understandings Influence Treatment Practicesmentioning
confidence: 99%